Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1203/00006450-200001000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Long Chain Polyunsaturated Fatty Acid Formation in Neonates: Effect of Gestational Age and Intrauterine Growth

Abstract: The present study was designed to evaluate the effect of gestational age and intrauterine growth on the long chain polyunsaturated fatty acid (LCP) synthesis from dietary precursors in neonates as reflected by plasma pools. These have been considered conditionally essential nutrients for normal growth, sensory maturation, and neurodevelopment. In vivo elongation/desaturation of deuterated d5-linoleic acid (d5-LA) to form arachidonic acid (AA), and d5-alpha-linolenic acid (d5-LNA) to form docosahexaenoic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(130 citation statements)
references
References 27 publications
3
121
0
2
Order By: Relevance
“…These findings suggest that although the fatty acid mix delivered to the fetus is largely determined by the fatty acid composition of the maternal blood, the placenta is able to preferentially transfer AA and DHA to the fetus by a combination of several mechanisms, as has recently been reviewed (Haggarty, 2002). Furthermore, although LC-PUFA synthesis from EFA precursors has been demonstrated to occur in preterm infants as early as 26-week gestation (Uauy et al, 2000), other reports have estimated that the contribution of endogenous synthesis to the total plasma LC-PUFA pool in term neonates is small (Demmelmair et al, 1995;Szitanyi et al, 1999).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These findings suggest that although the fatty acid mix delivered to the fetus is largely determined by the fatty acid composition of the maternal blood, the placenta is able to preferentially transfer AA and DHA to the fetus by a combination of several mechanisms, as has recently been reviewed (Haggarty, 2002). Furthermore, although LC-PUFA synthesis from EFA precursors has been demonstrated to occur in preterm infants as early as 26-week gestation (Uauy et al, 2000), other reports have estimated that the contribution of endogenous synthesis to the total plasma LC-PUFA pool in term neonates is small (Demmelmair et al, 1995;Szitanyi et al, 1999).…”
Section: Introductionmentioning
confidence: 84%
“…The synthesis of these fatty acids from EFA precursors by the fetus cannot be ruled out as contributing to the high proportion of AA and DHA in fetal circulation. The capacity for the metabolic elongation and desaturation of LA and ALA to form AA and DHA, respectively, has been consistently demonstrated to occur during the first days of life in humans, including very premature preterm neonates (Demmelmair et al, 1995;Carnielli et al, 1996;Salem Jr et al, 1996;Sauerwald et al, 1997;Szitanyi et al, 1999;Uauy et al, 2000), and it has also been shown to take place in fetal baboons (Su et al, 1999(Su et al, , 2001. Placental transfer of EPA (20:5(n-3)) has not been reported despite its growth inhibitor action (Sellmayer et al, 1996), its inhibitory effect on human placental membrane binding of EFA (Dutta-Roy, 2000) and its effect in reducing the availability of AA and its metabolites by a competition effect on pathways of EFA metabolism (Dutta-Roy, 1994), all of this denoting an important and active functional activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the level of DHA in the brain cortex and liver of preterm infants who died suddenly and that had been fed with artificial formulas was lower than of those fed with human milk (Farquharson et al, 1995). Nonetheless, recent in vivo studies using LA and LNA labelled with stable isotopes in at-term newborns, preterm infants and small for date infants have demonstrated that all infants are able to synthesise LC-PUFA (Demmelmair et al, 1995;Uauy et al, 2000). However, whether the amounts of AA and DHA synthesised are able to meet the daily requirements of infants, particularly in small for date infants, who exhibit the lowest rate of synthesis, is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The biomechanisms at the basis of these differences are actually under active investigation. In spite of the documented LC-PUFA biosynthesis in both preterm and term newborns, 9 the two major LC-PUFA (AA and DHA) in whole blood are already decreased at four days of life compared to cord levels Consumption and/or utilization rates higher than synthetic capacities of infants might explain these observations. Of interest, maternal n-3 LC-PUFA levels (including both EPA and DHA) are related to the n-3 LC-PUFA levels of cord but not of infants.…”
Section: Discussionmentioning
confidence: 91%